Immunity proteins of dual nuclease T6SS effectors function as transcriptional repressors. (30th March 2021) - Yadav, Sunil Kumar; Magotra, Ankita; Ghosh, Srayan; Krishnan, Aiswarya; Pradhan, Amrita; Kumar, Rahul; Das, Joyati; Sharma, Mamta; Jha, Gopaljee
Abstract: Bacteria utilize type VI secretion system (T6SS) to deliver antibacterial toxins to target co‐habiting bacteria. Here, we report that Burkholderia gladioli strain NGJ1 deploys certain T6SS effectors (TseTBg), having both DNase and RNase activities to kill target bacteria. RNase activity is prominent on NGJ1 as well as other bacterial RNA while DNase activity is pertinent to only other bacteria. The associated immunity (TsiTBg) proteins harbor non‐canonical helix–turn–helix motifs and demonstrate transcriptional repression activity, similar to the antitoxins of type II toxin–antitoxin (TA) systems. Genome analysis reveals that homologs of TseTBg are either encoded as TA or T6SS effectors in diverse bacteria. Our results indicate that a new ORF (encoding a hypothetical protein) has evolved as a result of operonic fusion of TA type TseTBg homolog with certain T6SS‐related genes by the action of IS3 transposable elements. This has potentially led to the conversion of a TA into T6SS effector in Burkholderia . Our study exemplifies that bacteria can recruit toxins of TA systems as T6SS weapons to diversify its arsenal to dominate during inter‐bacterial competitions. SYNOPSIS: Tox‐REase‐5 domain containing T6SS effectors of Burkholderia exhibit dual nuclease activity and cognate immunity proteins exert transcription repression activity, reminiscent of type II antitoxins. T6SS recruit intracellular toxins as extracellular weapons to target prey bacteria. TseTBg effector proteins of Burkholderia gladioli demonstrate RNase and host‐DNA methylation sensitive DNase activity. Associated immunity (TsiTBg) proteins have transcriptional repression activity and show similarity to type II TA antitoxins. The transposition of IS3 elements has potentially led to operonic fusion of TA and T6SS related genes. Ancestral toxin‐antitoxins of TA systems have been converted into T6SS effector‐immunity pairs. Abstract : Tox‐REase‐5 domain containing T6SS effectors of Burkholderia exhibit dual nuclease activity and cognate immunity proteins exert transcription repression activity, reminiscent of type II antitoxins. T6SS recruit intracellular toxins as extracellular weapons to target prey bacteria.